Geração REUNI: A participação juvenil no movimento estudantil na Universidade Federal de Alagoas –UFAL. - Lima, Simone Arestides de (2013)
This work focused on the youth policy participation in associative movements with collective meaning. For both, was chosen the University student movement in the Federal University of Alagoas, UFAL, by realizing this, the possibility of finding the object of this work. In this study, we investigated the reasons why young people/students entering the student movement, which the main forms of action, challenges and flags defended. Another important factor was the lifting of the historical trajectory of the movement in Brazil, abroad and in Alagoas, thus demonstrating their contributions to these societies.